2022
DOI: 10.1021/acsnano.2c07200
|View full text |Cite
|
Sign up to set email alerts
|

Nanocatalytic Biofunctional MOF Coating on Titanium Implants Promotes Osteoporotic Bone Regeneration through Cooperative Pro-osteoblastogenesis MSC Reprogramming

Abstract: An elevated bone microenvironmental reactive oxygen species (ROS) level is a hallmark of osteoporosis that often leads to the dysfunction of bone-related mesenchymal stem cells (MSCs), which would induce MSC senescence and severely undermine their osteoblastic potential. Herein, we report the in situ construction of bone microenvironment-responsive biofunctional metal–organic framework (bio-MOF) coating on the titanium surface through the coordination between p-xylylenebisphosphonate (PXBP) and Ce/Sr ions by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
47
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 53 publications
0
47
0
Order By: Relevance
“…Ling et al designed MoO3-xNUs to target the tumor environment to induce CAT-like reactions and generate cytotoxic superoxide radicals to induce apoptosis in tumor cells [ 89 ]. Coated organic backbone AHT-Ce/SrMOF containing Ce and Sr metal ions implanted in rats exhibited superoxide dismutase and catalytic peroxidase-like activity, activated AMPK signaling pathway, catabolized ROS in bone-related mesenchymal stem cells (BMSCs) and restored their mitochondrial function, and reversing the cellular senescence process [ 90 ]. At the same time, CaF2, a metal compound with peroxidase-like activity, can also be used as a nanoenzyme for tumor therapy.…”
Section: Therapeutic Strategies Using Mitochondria As Therapeutic Tar...mentioning
confidence: 99%
“…Ling et al designed MoO3-xNUs to target the tumor environment to induce CAT-like reactions and generate cytotoxic superoxide radicals to induce apoptosis in tumor cells [ 89 ]. Coated organic backbone AHT-Ce/SrMOF containing Ce and Sr metal ions implanted in rats exhibited superoxide dismutase and catalytic peroxidase-like activity, activated AMPK signaling pathway, catabolized ROS in bone-related mesenchymal stem cells (BMSCs) and restored their mitochondrial function, and reversing the cellular senescence process [ 90 ]. At the same time, CaF2, a metal compound with peroxidase-like activity, can also be used as a nanoenzyme for tumor therapy.…”
Section: Therapeutic Strategies Using Mitochondria As Therapeutic Tar...mentioning
confidence: 99%
“…For the treatment of osteoporosis, Chen et al constructed microenvironmentally responsive biofunctional metal-organic framework (bioMOF) coatings in situ by hydrothermal method on titanium surface through the coordination of phydroxydiphosphonate (PXBP) and cerium (Ce)/strontium (Sr) ions. Specifically, Ce ions can exhibit catalytic properties similar to CAT and SOD to break down ROS in MSCs and restore their mitochondrial function (100). In addition, several studies have demonstrated that Sr can promote CAT/SOD activity and regulate mitochondrial dynamics, thereby enhancing diabetic osseointegration (101).…”
Section: Strategies For Restoring Mitochondrial Homeostasis 231 Exces...mentioning
confidence: 99%
“…Some researchers constructed a biofunctional metal–organic framework coating on the surface of Ti implants using hydrothermal binding Ce/Sr ions with xylene bisphosphonate. This modification effectively enhanced in situ functional recovery and the osteogenesis of mesenchymal stem cells …”
Section: Introductionmentioning
confidence: 99%
“…This modification effectively enhanced in situ functional recovery and the osteogenesis of mesenchymal stem cells. 20 The metal ion surface modification of implants using metal NP coatings or their compounds has also been applied 21 for enhanced surface morphology and biological properties. NP surface modification can improve the osseointegration activity.…”
Section: Introductionmentioning
confidence: 99%